1988
DOI: 10.1007/bf01807282
|View full text |Cite
|
Sign up to set email alerts
|

Morphometric evaluation of microvessels surrounding hyperplastic and neoplastic mammary lesions

Abstract: Size and density of microvessels in close proximity to normal, hyperplastic, and in situ neoplastic mammary epithelium were evaluated with a morphometric method. Human tissue samples were obtained from breast mammoplasty or biopsy specimens with diagnosis of either epitheliosis or ductal carcinoma in situ. The mean vessel size was significantly enhanced in hyperplastic and neoplastic lesions as compared to mammoplasty specimens considered as 'normal'. On the contrary, the density of the microvessels around the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
30
0
2

Year Published

1997
1997
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(32 citation statements)
references
References 24 publications
(21 reference statements)
0
30
0
2
Order By: Relevance
“…Discussion of candidate mechanisms that could account for the observed reduction in vascular density attributed to dietary energy restriction is somewhat problematic given the difficulty of inferring mechanisms from vascular density data collected from a single time point at the end of a study (20,26,27). However, as outlined in (20), the procedures used for vascular density analysis, i.e., the classifica- .…”
Section: Discussionmentioning
confidence: 99%
“…Discussion of candidate mechanisms that could account for the observed reduction in vascular density attributed to dietary energy restriction is somewhat problematic given the difficulty of inferring mechanisms from vascular density data collected from a single time point at the end of a study (20,26,27). However, as outlined in (20), the procedures used for vascular density analysis, i.e., the classifica- .…”
Section: Discussionmentioning
confidence: 99%
“…At the outset of this study, a review of the literature indicated that antiserum directed against Factor VIII was selected in most work in which immunostaining was being used to detect blood vessels in mammary tissue (Ottinetti and Sapino 1988;Fregene et al 1993;Guidi et al 1994;Guinebretiere et al 1994;Heffelfinger et al 1996Heffelfinger et al , 2000. Because the goal of methods development was to quantify all blood vessels, which we now know spanned a range from a cross-sectional area of 2.5 m 2 to 0.12 mm 2 , it was decided to compare Factor VIII staining with that obtained using antiserum directed against the CD31 epitope, which has been reported to be more consistently expressed on developing capillaries than is Factor VIII (reviewed in Vermeulen et al 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Most information that does exist is either qualitative, describing the nature of the vascular beds, or focuses on the occurrence of microvessels. Moreover, the majority of work in the mammary gland using immunohistochemical (IHC) approaches to detect blood vessels has been done using Factor VIII (Ottinetti and Sapino 1988;Fregene et al 1993;Guidi et al 1994;Guinebretiere et al 1994;Heffelfinger et al 1996Heffelfinger et al , 2000, whereas, work in other model systems indicates that CD31 is the most sensitive and specific endothelial marker for vascular endothelium and is the recommended epitope for these types of studies (Vermeulen et al 1996).…”
mentioning
confidence: 99%
“…2 We and others have shown that angiogenesis is also important in the process of breast cancer formation, as indicated by the stepwise increase in microvascular density with progression from normal epithelium to invasive disease. [3][4][5][6] In addition, we have shown that in the rat model system of DMBA-induced mammary tumor formation there is a similar pattern of upregulated microvascular density with progression. 7 Finally, if one isolates normal epithelium or tumor tissue from DMBA-treated rats, both are capable of inducing endothelial tubule formation in vitro, indicating that the angiogenic potential of these tissues is greater than that from vehicle-treated control rats.…”
mentioning
confidence: 95%